2018
DOI: 10.1126/sciadv.aau2104
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assembly of liquid crystalline graphene oxide gel fibers for ion transport

Abstract: Highly aligned GO gel fibers are fabricated under high extensional flow for efficient nanofluidic transport of ion species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 49 publications
0
82
0
Order By: Relevance
“…To fabricate more ordered laminar structure with the minimal number of nonidealities (imperfect stacking, folding, and wrinkles), 2D nanosheets should be kept horizontally aligned when depositing over each other. Besides adjusting intersheet interactions, external forces such as centrifugal, shear, compressive, and even magnetic forces may be employed in this process . 3) Transporting Mechanism : It is obvious that most studies so far endeavor to explain the mass transporting behaviors in horizontal channels including interlayer capillaries and wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…To fabricate more ordered laminar structure with the minimal number of nonidealities (imperfect stacking, folding, and wrinkles), 2D nanosheets should be kept horizontally aligned when depositing over each other. Besides adjusting intersheet interactions, external forces such as centrifugal, shear, compressive, and even magnetic forces may be employed in this process . 3) Transporting Mechanism : It is obvious that most studies so far endeavor to explain the mass transporting behaviors in horizontal channels including interlayer capillaries and wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a systematic analysis of the electro-optical response of GO LCs under alternating fields was presented by Guerrero et al [378] and a shear-induced stripe assembly was reported by Hong et al [379]. Due to these intriguing physical properties, various potential applications based on GO LCs (Figure 15c-e), such as GO LC gels with "shape memory" effect [380], photoluminescence imaging [381], nanocomposites [382][383][384], sensitive strain sensors [385], transparent electrodes [386], conductive fibres [387][388][389][390], multifunctional yarns [391] and membranes [392], flame-retardant nanocoatings [393], optical devices [394] and biomedical applications [395], have been anticipated and some of them have been realized. More relevant information can be found in a recent review published by Sasikala et al [396].…”
Section: Lc-aided-assembly and Self-assembly Of Nanomaterialsmentioning
confidence: 92%
“…This strategy allows the cost‐effective production of 2D‐NLMs with tunable nanochannels at large scale . Given the ease of synthesis, high‐level structural tunability and versatility, 2D‐NLMs have been extensively explored for confined molecular and ion transport by many research groups including Gao, Geim, Gogotsi, Guo, Huang, Jin, Li, Mi, Nair, Ren, Zhu, and more. The following section will lay out some of the typical attributes of 2D‐NLMs obtained by cascading to correlate with the advances in solvation‐involved nanoionics research.…”
Section: Constructing Void Nanostructures For Nanoionics From 2d Nanomentioning
confidence: 99%
“…The solution processability of 2D nanomaterials is particularly attractive for application‐related research. First, large‐area fabrication of 2D‐NLMs can be readily achieved via ordinary liquid processing techniques including filtration, spinning, and casting, facilitating the translation of their unique ionic behaviors into real‐world applications. Second, the thickness of 2D‐NLMs can be made exceptionally thin, down to ≈10 nm.…”
Section: Potential Of 2d‐nlms For Solvation‐involved Nanoionicsmentioning
confidence: 99%
See 1 more Smart Citation